IMPLEMENTASI PROGRAM DAPUR SEHAT ATASI STUNTING TERHADAP PENURUNAN STUNTING DI KOTA BATAM - Pratiwi, Diah Ayu; Nadia; Sari, Meri Enita Puspita; Solihin , Muhammad (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
Stunting is an urgent problem that needs to be addressed by the Indonesian Government as it affects the quality of the nation's generation. A quality generation is one of the indicators of successful human development. One of the programmes implemented by the government to address stunting is the Dapur Sehat Atasi Stunting (DASHAT) programme. The DASHAT program is a community empowerment initiative that aims to meet the balanced nutritional needs of families at risk of stunting, including brides-to-be, pregnant women, nursing mothers, and toddlers at risk of stunting, especially for underprivileged families, through the use of local food resources and ingredients. This study aims to investigate the implementation of DASHAT programme in Batam City. This research uses a qualitative research method with the research location conducted in Kampung KB Sambau Village. Selection of informants was carried out in a purposive manner. Data analysis is done simultaneously with data collection. Includes understanding the data, doing inductive coding, grouping codes into themes, making reports. Data validity with triangulation and member checking. The results showed that the implementation of the DASHAT program in Batam City is characterised by various challenges such as most KB villages in Batam City have not realised the DASHAT program, budget constraints, lack of a program mobilisation team and the need for increased coordination between program implementing agencies. Therefore, there is a need for increased coordination between stakeholders and an adequate budget as an effort to tackle stunting. The involvement of the private sector and the community in the DASHAT programme needs to be increased, because the problem of stunting is not only the government's business, but the business of all parties.